Thresholds of freshwater biodiversity in response to riparian vegetation loss in the Neotropical region. Issue 7 (29th May 2020) - Dala‐Corte, Renato B.; Melo, Adriano S.; Siqueira, Tadeu; Bini, Luis M.; Martins, Renato T.; Cunico, Almir M.; Pes, Ana M.; Magalhães, André L. B.; Godoy, Bruno S.; Leal, Cecília G.; Monteiro‐Júnior, Claudio S.; Stenert, Cristina; et al.
Abstract: Protecting riparian vegetation around streams is vital in reducing the detrimental effects of environmental change on freshwater ecosystems and in maintaining aquatic biodiversity. Thus, identifying ecological thresholds is useful for defining regulatory limits and for guiding the management of riparian zones towards the conservation of freshwater biota. Using nationwide data on fish and invertebrates occurring in small Brazilian streams, we estimated thresholds of native vegetation loss in which there are abrupt changes in the occurrence and abundance of freshwater bioindicators and tested whether there are congruent responses among different biomes, biological groups and riparian buffer sizes. Mean thresholds of native vegetation cover loss varied widely among biomes, buffer sizes and biological groups: ranging from 0.5% to 77.4% for fish, from 2.9% to 37.0% for aquatic invertebrates and from 3.8% to 43.2% for a subset of aquatic invertebrates. Confidence intervals for thresholds were wide, but the minimum values of these intervals were lower for the smaller riparian buffers (50 and 100 m) than larger ones (200 and 500 m), indicating that land use should be kept away from the streams. Also, thresholds occurred at a lower percentage of riparian vegetation loss in the smaller buffers, and were critically lower for invertebrates: reducing only 6.5% of native vegetation cover within a 50‐m riparian buffer is enough to cross thresholds for invertebrates. Synthesis and applications . The high variability in biodiversity responses to loss of native riparian vegetation suggests caution in the use of a single riparian width for conservation actions or policy definitions nationwide. The most sensitive bioindicators can be used as early warning signals of abrupt changes in freshwater biodiversity. In practice, maintaining at least 50‐m wide riparian reserves on each side of streams would be more effective to protect freshwater biodiversity in Brazil. However, incentives and conservation strategies to protect even wider riparian reserves (~100 m) and also taking into consideration the regional context will promote a greater benefit. This information should be used to set conservation goals and to create complementary mechanisms and policies to protect wider riparian reserves than those currently required by the federal law. Abstract : The high variability in biodiversity responses to loss of native riparian vegetation suggests caution in the use of a single riparian width for conservation actions or policy definitions nationwide. The most sensitive bioindicators can be used as early warning signals of abrupt changes in freshwater biodiversity. In practice, maintaining at least 50‐m wide riparian reserves on each side of streams would be more effective to protect freshwater biodiversity in Brazil. However, incentives and conservation strategies to protect even wider riparian reserves (~100 m) and also taking into consideration the regional context will promote a greater benefit. This information should be used to set conservation goals and to create complementary mechanisms and policies to protect wider riparian reserves than those currently required by the federal law. Resumo: Proteger a vegetação no entorno de riachos é vital para reduzir os efeitos das mudanças ambientais sobre os ecossistemas aquáticos e para a manutenção de sua biodiversidade. Assim, a identificação de limiares ecológicos é útil para regular os limites de uso e para orientar o manejo de zonas ripárias, visando a conservação da biota aquática. Usando dados de peixes e invertebrados aquáticos de pequenos riachos do Brasil, nós estimamos os limiares de perda de vegetação nativa nos quais ocorrem mudanças abruptas na ocorrência e abundância de bioindicadores aquáticos. Também testamos se existem respostas congruentes entre os diferentes biomas, grupos biológicos e áreas de vegetação ripária ( buffers ). Os valores médios dos limiares de perda de vegetação nativa variaram marcadamente entre biomas, tamanhos de buffer e grupos biológicos: entre 0, 5% e 77, 4% para peixes, entre 2, 9% e 37, 0% para invertebrados aquáticos e entre 3, 8% e 43, 2% para um subconjunto de invertebrados aquáticos. Os intervalos de confiança dos limiares foram amplos, mas os valores mínimos dos intervalos foram reduzidos para os menores buffers ripários (50 e 100 m) em comparação com os maiores (200 e 500 m), indicando que o uso do solo deve ser mantido longe dos riachos. Além disso, os limiares ocorreram em menores porcentagens de perda de vegetação ripária nos buffers menores, e foram criticamente baixos para invertebrados aquáticos: uma redução de apenas 6, 5% da cobertura de vegetação nativa no buffer ripário de 50 m é suficiente para ultrapassar os limiares de perda de invertebrados. Síntese e aplicações . A elevada variabilidade dos limiares de declínio abrupto da biodiversidade aquática em resposta a perda de vegetação ripária nativa sugere cautela no uso de uma largura única de proteção ripária para ações de conservação e definição de políticas nacionais. Os bioindicadores mais sensíveis podem ser usados como sinais precoces que alertam a aproximação de mudanças abruptas na biodiversidade aquática. Na prática, manter reservas ripárias (áreas de preservação permanente—APP) de pelo menos 50 m de largura, em ambos os lados dos riachos, parece ser mais efetivo em proteger a biodiversidade de água doce do Brasil. Contudo, incentivos e estratégias de conservação que protejam reservas ripárias ainda maiores (~100 m de largura) e que levem em consideração o contexto regional podem promover um maior benefício. Essas informações podem ser usadas para definir metas de conservação e para criar mecanismos e políticas complementares para proteger reservas ripárias (APP) ainda maiores do que aquelas atualmente requeridas pela lei federal.